Адаптивная схема для оценки влияния разномасштабных факторов на качество воды (Географический вестник=Geographical bulletin, 2017)
Предложен метод, включающий несколько методик для последовательного дифференцирования нагрузок, ведущих к ухудшению качества воды. Данный метод был экспериментально применен на небольшом, но очень гетерогенном водосборе во Фландрии (Бельгия). Значительное снижение затрат на развитие детальных процесс-ориентированных моделей может быть достигнуто при применении метода баланса потоков вещества (MFA) на стадии камеральной рекогносцировки. Невязки в балансе могут быть значительно уменьшены за счет корректировки оцененных величин при помощи измерений. Анализ конкретного примера подтвердил, что оценка качества воды и основанная на данных о сбросах характеристика должны быть выполнены совместно, так как улучшение качества сбрасываемых вод не всегда ведет к улучшению качества воды.ATV. (2004). Arbeitsbericht der ATV-DVWK-Arbeitsgruppe 5.6: Signifikante Nährstoffeinträge aus der Fläche. ATV-DVWK- Arbeitsgruppe 5.6 "Diffuse Stoffeinträge", Hennef.Behrendt, H., Huber, P., Ley, M., Opitz, D., Schmoll, O., Scholz, G., and Uebe, R. (1999). Nährstoffbilanzierung der Flußgebiete Deutschlands - UBA-Forschungsbericht. (Nutrient balancing of river basins in Germany - UBA research report.).Blumensaat, F., Tranckner, J., Hoeft, S., Jardin, N., and Krebs, P. (2009). Quantifying effects of interacting optimisation measures in urban drainage systems. Urban Water Journal, 6(2), 93-105.BMU. (2005). Umweltpolitik. Die Wasserrahmenrichtlinie - Ergebnisse der Bestandsaufnahme 2004 in Deutschland. Bundesministerium für Umwelt, Naturschutz und Reaktorsicherheit, Paderborn.Bodnarchuk, T. BASELINE ASSESSMENT OF WATER CONTAMINATION IN UKRAINIAN PART OF WESTERN BUG BASIN. http://europeicid2009.org/, Ivano-Frankivsk.Borchardt, D., Bürgel, B., Durchschlag, A., Grottker, M., Halle, M., Podraza, P., Schitthelm, D., Tetzlaff, D., and Uhl, M. (2008). Merkblatt BWK-M7: Detaillierte Nachweisführung immissionsorientierter Anforderungen an Misch- und Niederschlagswassereinleitungen gemäß BWK-Merkblatt 3. Bund der Ingenieure für Wasserwirtschaft, Abfallwirtschaft und Kulturbau (BWK) e.V., Stuttgart.De Pauw, N. and Heylen, S. (2001). Biotic index for sediment quality assessment of watercourses in Flanders, Belgium. Aquatic Ecology, 35(2), 121.EEA. (1999). Environment in the European Union at the turn of the century.FWR. (1998). Urban Pollution Management Manual. Second Edition. Report No. FR/CL 009, Foundation for Water Research, Marlow.Grambow, M. (2008). Wassermanagement - Integriertes Wasserressourcenmanagement von der Theorie zur Umsetzung, Friedr. Vieweg & Sohn Verlag, Wiesbaden.Helm, B., Tränckner, J., Sieker, H., and Krebs, P. (2009). Flexibilität als Bewertungskriterium bei der Planung von Systemen der Regenentwässerung. Korrespondenz Abwasser, 56, p. 372-381.HMULV. (2004). Leitfaden für das Erkennen ökologisch kritischer Gewässerbelastungen durch Abwassereinleitungen. Hessisches Ministerium für Umwelt, ländlichen Raum und Verbraucherschutz, Wiesbaden.Lammersen, R. (1997). Die Auswirkungen der Stadtentwässerung auf den Stoffhaushalt von Fließgewässern. Schriftenreihe für Stadtentwässerung und Gewässerschutz, SuG Verlagsgesellschaft, Hannover.Merz, R. and Buck, W. (1997). Verfahren zur Entscheidungsfindung bei Mehrfachzielsetzung sowie Zielsysteme und Zielkriterien für die Planung und Bewertung wasserwirtschaftlicher Maßnahmen. Institut für Wasserwirtschaft und Kulturtechnik, Universität Karlsruhe, Karlsruhe.Muschalla, D., Schutze, M., Schroeder, K., Bach, M., Blumensaat, F., Gruber, G., Klepiszewski, K., Pabst, M., Pressl, A., Schindler, N., Solvi, A. M. and Wiese, J. (2009). The HSG procedure for modelling integrated urban wastewater systems. Water Science and Technology, 60(8), 2065-2075.UNESCO. (2009). IWRM Guidelines at River Basin Level, Tokyo.AN ADAPTIVE FRAMEWORK TO DIFFERENTIATE WATER QUALITY IMPACTS ON A MULTI-SCALE LEVELThe identification of options for an efficient resource management requires tools of different complexity. A reliable performance evaluation for future management scenarios is often constrained by i) data availability and ii) the willingness to invest resources in a detailed process analysis. The inherent conflict to provide reliable decision support for complex questions with a minimum of effort increases the risk to base decisions upon uncertain and unverified conclusions. This paper proposes a systematic methodology that combines several tools to stepwise differentiate pressures that lead to water quality deterioration. The method is applied to a small, but heterogeneous catchment in Flanders (Belgium). It is shown that, despite its deficiencies, MFA can be used efficiently for screening purposes to ultimately reduce the effort spent on developing detailed process models. Uncertainty associated with mass flow balancing can be reduced significantly when backing up estimations by reliable measurements. The case study analysis confirmed that water quality and emission based performance evaluation cannot be done separately as an emission-based performance improvement does not necessarily lead to an improved water quality.K e y w o r d s: IWRM; integrated modeling; mass balancing; water quality impacts; diffuse sources; point sources; GIS.